Skeletal Muscle Mass Change During Chemotherapy: A Systematic Review and Meta-analysis - JANG, MIN KYEONG; PARK, CHANG; HONG, SUSAN; LI, HONGJIN; RHEE, ESTHER; DOORENBOS, ARDITH Z. (Anticancer research, 2020)
Skeletal muscle mass loss is an emerging concern in oncology. Our systematic review and meta-analysis identified the mean difference in skeletal muscle index pre- to post-chemotherapy and synthesized potential key factors. We searched primary original research published through October 2019 in four databases: MEDLINE via PubMed, Scopus, CINAHL, and Embase. Fifteen studies were included, 60% published in the past 2 years (2018-2019). Advanced non-small cell lung cancer was the most frequently reported cancer, and overall survival the most often identified key related factor. Mean difference in skeletal muscle index during chemotherapy was 2.72 (95%CI=1.77-3.67, p=0.00), with muscle loss in males (4.52, 95%CI=3.34-5.71, p=0.00) about 1.6 times higher than that in females (2.86, 95%CI=0.81-4.92, p=0.01). Oncologists should recognize sex-specific differences in skeletal muscle mass loss during chemotherapy and consider adjusting treatment accordingly.